2012
DOI: 10.1016/j.ijmedinf.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of a computerized clinical decision support system for asthma by pediatric pulmonologists

Abstract: Purpose To investigate use of a new guideline-based, computerized clinical decision support (CCDS) system for asthma in a pediatric pulmonology clinic of a large academic medical center. Methods We conducted a qualitative evaluation including review of electronic data, direct observation, and interviews with all nine pediatric pulmonologists in the clinic. Outcome measures included patterns of computer use in relation to patient care, and themes surrounding the relationship between asthma care and computer u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…The asthma guideline from the National Heart Lung and Blood Institute (NHLBI)[3] focuses mainly on the outpatient environment, but includes information on care for emergency exacerbations. The most frequent approach to implementing guidelines in a clinical environment is still paper-based [6], but computer-based implementations are also used [7, 8]. Researchers have examined the benefits of paper-based and computer-based guideline implementations, but sustainable computer-based approaches in a clinical environment remain infrequent.…”
Section: Introductionmentioning
confidence: 99%
“…The asthma guideline from the National Heart Lung and Blood Institute (NHLBI)[3] focuses mainly on the outpatient environment, but includes information on care for emergency exacerbations. The most frequent approach to implementing guidelines in a clinical environment is still paper-based [6], but computer-based implementations are also used [7, 8]. Researchers have examined the benefits of paper-based and computer-based guideline implementations, but sustainable computer-based approaches in a clinical environment remain infrequent.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have developed such tools but have largely focused on implementation rather than actual effect on clinical outcomes. 27,28 Decision support tools are often unwieldy for prescribers to use because of the need to shift from paper-based to electronic-based data collection, complex interfaces, and lack of direct linkage from control assessment to suggested treatment. 9,14,29,30 An asthma decision support tool similar to the ACET Program was integrated into the EHR (EPIC) at a large children's hospital through a link to an external Internet-based program.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have shown that adoption of a CCDSS may be challenging, [5][6][7] this study showed the benefit of a CCDSS. Knowing that workflow constraints and technical expertise are known barriers to CCDSS use, 8 a CCDSS was created that took into account the flow of the patient visit and need for information at the point of care. The study CCDSS helped clinicians think about appropriate exam elements and served as a refresher prior to patient evaluation.…”
Section: Discussionmentioning
confidence: 99%